Raising global competitiveness of Tamil Nadu's IT industry - Bajpai, Nirupam; Radjou, Navi (2000)
In the emerging knowledge-based global economy, the sustainable competitive advantage of nations will reside not in their possession of natural resources or cheap labour force, but in their ability to harness their countries' intellectual assets. As such, the knowledge revolution offers a unique chance to leapfrog entire stages of development. This paper argues that in order to make such a leap Tamil Nadu needs to initiate a knowledge-led development policy that builds on the state's successful IT industry. This paper proposes a roadmap to raise the global competitiveness of Tamil Nadu's IT industry, through strengthening both the demand and the supply. - Reproduced
Keywords: Information technology - India - Tamil Nadu; Information technology